EVALUASI PELAKSANAAN JAMINAN KESEHATAN NASIONAL - Arip Suprianto; Dyah Mutiarin (Journal of Governance and Public Policy, 2017)
Health care is one of the fundamental rights of the people who held the government as mandated in the 1945 ConstitutionArticle 28H Paragraph (1) Everyone has the right to live physically and mentally prosperous, residence and got a goodenvironment and healthy and receive medical care. Social Security Agency consists of BPJS BPJS Health and Employmentwhich will cover the entire population of Indonesia no later than January 1, 2019. Services BPJS many people questioned.According to Assistant Representative ORI D.I.Y. Reports BPJS services complaints procedure is quite high in 2015. Thereare also complaints of them in the management of the bureaucracy, registration, until the queues are long and the relatedpayment. Of the existing problems researchers aim to investigate the implementation of the National Health Insurance(JKN) focused on Stakeholder Relations, Financing Model and Outcome JKN in Bantul. This research approach using acombination of methods. The research location in the district of Bantul. Sources of data in this study are primary data andsecondary data. Data collection techniques in this study using interview, questioner and documentation. The unit of dataanalysis in this study is the Social Security Agency. The sampling technique using the formula Slovin. Data analysistechniques in this study using data reduction, data presentation and conclusion. According to the research there is arelationship between BPJS with Health Facilities regulated in PP No.85 Year 2013 on cooperation in improving healthservices. Hospitals and health centers in collaboration with BPJS had been running quite positive. A total of 90 healthfacilities in Bantul who cooperate with BPJS. Of health insurance financing model thats enough ideal assessed on the indexaverage of 2.74 included in either category. JKN one principle of mutual assistance means helping each one participant tothe other participants. While the outcome JKN assessed on the percentage of the guarantee of health in Indonesia (52.5%)in the province D.I.Y. (64.6%) and in Bantul (73%). Tinkat Bantul merepon public awareness by becoming participantsBPJS. Service is guaranteed for the First level services and advanced stipulated in Presidential Decree No. 19 Year 2016.And the cost of minor health for the poor. Of the average index value JKN outcome of 3:06 categorized as either couldmean that JKN program has considerable benefits for both participants.